Selection strategies for discontinuous innovation - Bessant, John; von Stamm, Bettina; Möslein, Kathrin (International Journal of Technology Management, 2011)
Learning to manage innovation is essentially about developing and modifying capability to search, select and implement and being able to repeat the trick. Developing {textquoteleft}routines{textquoteright} which allow for regular innovative activity is central to capability building {textendash} but the paradox is that as the firm routinises so its ability to cope with the unexpected diminishes. Successful innovating organisations also require the ability to review those routines and extend or change them. We suggest that discontinuous innovation highlights this problem of dynamic capability in that it forces firms to learn new approaches and let go of old ones around the core search, select and implement questions. In this paper, we explore the challenge of extending and replacing routines for {textquoteleft}selection{textquoteright} in the face of discontinuous challenges and highlight the problems of {textquoteleft}bounded space{textquoteright} within which both explore and exploit routines operate but which are insufficient to cope with challenges in discontinuity.
WiSo-Import:2015-03-26:2040